2002
DOI: 10.1128/jvi.76.2.484-491.2002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sterilizing Immunity to Rinderpest in Cattle Vaccinated with a Recombinant Vaccinia Virus Expressing High Levels of the Fusion and Hemagglutinin Glycoproteins

Abstract: Rinderpest is an acute and highly contagious viral disease of ruminants, often resulting in greater than 90% mortality. We have constructed a recombinant vaccinia virus vaccine (v2RVFH) that expresses both the fusion (F) and hemagglutinin (H) genes of rinderpest virus (RPV) under strong synthetic vaccinia virus promoters. v2RVFH-infected cells express high levels of the F and H glycoproteins and show extensive syncytium formation. Cattle vaccinated intramuscularly with as little as 10 3 PFU of v2RVFH and chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…1) using homologous recombination (19) and transient dominant selection (20). One rVACV expresses the RVFV glycoproteins (Gn and Gc) under the control of a strong VACV synthetic promoter (vCOGnGc) (17,21) and the second expresses the human IFN-γ (HuIFNγ) gene in addition to the two RVFV glycoproteins (vCOGnGcγ). The HuIFNγ gene was added to enhance safety for human vaccinators (22,23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) using homologous recombination (19) and transient dominant selection (20). One rVACV expresses the RVFV glycoproteins (Gn and Gc) under the control of a strong VACV synthetic promoter (vCOGnGc) (17,21) and the second expresses the human IFN-γ (HuIFNγ) gene in addition to the two RVFV glycoproteins (vCOGnGcγ). The HuIFNγ gene was added to enhance safety for human vaccinators (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has extensive experience in developing rVACVs for the control of a number of human and animal diseases (17,18,22,24,34,35). Multiple approaches have been used to enhance the safety of poxviruses, including deletion or insertional inactivation of genes that enhance virulence, expression of cytokines, development of replication-deficient VACVs, such as MVA and NYVAC, or host cell-restricted vectors, such as canarypox and fowlpox (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of single VV [38] and Capri poxvirus vectors [39] expressing either the F or H protein of RPV, showed anamnestic responses that indicated replication of the challenge virus shortly after challenge, and long-term studies showed only partial protection [40]. In contrast, the double vaccinia recombinant expressing both the F and H proteins of PPRV v2RVFH provided complete protection with sterilizing immunity during both short-and long-term studies [41].…”
Section: Animal Studies and Serologymentioning
confidence: 99%
“…In order to evaluate vaccine efficiency, we constructed a VV (WR strain) expressing SIV Gag-Pol to be used as a surrogate challenge (2,46). The gag-pol open reading frame was cloned by PCR and inserted under the dsP which were previously demonstrated to result in increased levels of expression compared to VV natural promoters (49). The gag-pol fragment was then introduced into the VV genome through homologous recombination and insertional inactivation of the VV B8R gene, generating vSIVgag-pol.…”
Section: Construction Of Ifn-␥-expressing Pseudotyped Single-cycle Sivsmentioning
confidence: 99%